George Eliot and the conflict of interpretations a reading of the novels - Carroll, David (Cambridge Univ. Press, 1992)
Two versions of George Eliot, both very influential, have emerged from the study of her life and work. One is the radical Victorian thinker, formidably learned in a whole range of intellectual disciplines, to which she made major contributions during her early years in London. The other is the reclusive novelist, enigmatic, sybilline, celebrating through her fiction the communal values which were being eroded in the modern world. This study brings the two together, and by placing her within the crisis of belief and value acted out in the mid-nineteenth century, it reveals the unity of her whole career. George Eliot saw this crisis as one of interpretation, and the intensity of her writing comes from the vivid, almost apocalyptic, awareness that traditional modes of interpreting the world were breaking down irrevocably. This study shows how, in response to this, she redefined the nature of Victorian fiction--its presentation of character, the role of the narrator, the structure of narrative, the depiction of social and historical change. Each of her novels becomes an experiment which tests to the point of destruction a variety of Victorian myths, orthodoxies and ideologies, as it moves towards its climax--the inevitable contradiction which disconfirms all theories of life. George Eliot and the conflict of interpretations articulates the tension, novel by novel, between the writer's suspicion of orthodox creeds and her urgent need to restore values in a sceptical age. Each attempt to break through the conflict of interpretations acknowledges the urgency of the need and the provisional nature of any resolution.
Keywords: Eliot, George <1819-1880>; Eliot, George <1819-1880> - Critique et interprétation; Eliot, George <1819-1880> -- Criticism and interpretation; Eliot, George -- 1819-1880; Geschichte 1800-1900; Romance ingles; Geschichte; Didactic fiction, English -- History and criticism; Women and literature -- England -- History -- 19th century; Roman